PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN KETERLIBATAN KERJA TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR SEBAGAI VARIABEL MEDIASI - Maharani, Wilia Krisna; Kharismasyah, Alfato Yusnar; Darmawan, Akhmad; Innayah, Maulida Nurul (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of Perceived Organizational Support (POS) and Work Engagement on Employee Performance through the mediating role of Organizational Citizenship Behavior (OCB). The research was conducted at PT. Central Sandang Jayatama Cilacap, with a total population of 800 employees. Using the accidental sampling technique, 160 employees were selected as respondents. Data were collected through a structured questionnaire and analyzed using the SmartPLS software. The results indicate that POS and Work Engagement have a significant effect on both OCB and Employee Performance. Furthermore, OCB effectively mediates the relationship between POS and Work Engagement with Employee Performance. These findings highlight the importance of organizational support and employee engagement in enhancing performance through OCB. This study contributes to the development of human resource strategies in the garment manufacturing sector by promoting a supportive work environment and proactive employee behavior.